2013
DOI: 10.1038/ki.2013.182
|View full text |Cite
|
Sign up to set email alerts
|

Unmeasured anions and cations in advanced chronic kidney disease

Abstract: (T4C), rs6497476 (A4G), and rs4293393 (T4C). What led us to the awkwardness of mixing strands? We initially considered that, in many previous reports on UMOD, investigators were accustomed to referring to rs13333226 A/G (antisense strand), rs6497476 T/C (antisense strand), and rs4293393 C/T (sense strand), and we wanted to remain consistent with past nomenclature. But clearly we created more confusion than clarity. We hope that Figures 1a and b begin to clarify the strand issues. Q-2: The second question was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…3 Previously, we have demonstrated hyperchloremia impact on metabolic acidosis of up to 43% of CKD patients. 2 Moreover, it is known that metabolic acidosis has detrimental effects on nutrition 4 and in the pathogenesis of secondary hyperparathyroidism. 5 Several studies have demonstrated a correlation between serum bicarbonate with nutritional status and CKD-related bone disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Previously, we have demonstrated hyperchloremia impact on metabolic acidosis of up to 43% of CKD patients. 2 Moreover, it is known that metabolic acidosis has detrimental effects on nutrition 4 and in the pathogenesis of secondary hyperparathyroidism. 5 Several studies have demonstrated a correlation between serum bicarbonate with nutritional status and CKD-related bone disorders.…”
Section: Introductionmentioning
confidence: 99%
“…1 Most patients with CKD-associated metabolic acidosis have higher serum anion gap because of the accumulation of unmeasured anions (UA); however, in many patients, CKD is also associated with hyperchloremic acidosis even in advanced stages. 2 According to the quantitative physicochemical approach to acid-base disorders, hyperchloremia leads to metabolic acidosis due to a reduction in strong ion difference (SID). 3 Previously, we have demonstrated hyperchloremia impact on metabolic acidosis of up to 43% of CKD patients.…”
Section: Introductionmentioning
confidence: 99%